Oscillatory and Asymptotic Behavior of Nonlinear Functional Dynamic Equations of Third Order. (15th June 2022) - Hassan, Taher S.; Attiya, Adel A.; Alshammari, Mohammad; Abdel Menaem, Amir; Tchalla, Ayékotan; Odinaev, Ismoil
Abstract : The purpose of this work is to derive sufficient conditions for the oscillation of all solutions of the third-order functional dynamic equation p 2 ξ ϕ γ 2 p 1 ξ ϕ γ 1 y Δ ξ Δ Δ + p ξ ϕ β y g ξ = 0, on a time scale T . In addition, we present some Hille-type conditions for generalized third-order dynamic equations that improve and extend significant contributions reported in the literature without imposing time-scale restrictions. An example is given to demonstrate the essential results.